(untitled) (Sudurpaschim Spectrum, 2023)
Foreign aid is an important factor for the rapid economic development, growth, and fulfillment of resource gaps in developing countries like Nepal. This paper analyzes the contribution of foreign aid and other foreign inflows of capital like foreign direct investment (FDI) and remittances to the GDP of Nepal. This paper examines the role of foreign aid on the economic growth of Nepal by using secondary time series data from 1996/97 to 2019/20. This paper also used the data series of the same period for trend analysis of foreign aid in Nepal. The secondary data obtained from the World Bank-World Development Indicator has been analyzed using ordinary least squares regression. This paper uses GDP as a dependent variable, foreign aid as a major independent variable, and FDI and remittances as supporting independent variables. The empirical results of this paper prove that there is a positive and significant relationship between GDP and foreign aid inflow to Nepal. The empirical results also prove that there is a positive and significant relationship between GDP and remittances. Similarly, there is also a positive and significant relationship between GDP and FDI.